2011
DOI: 10.1245/s10434-011-1826-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of the Status of Sentinel Lymph Nodes in Melanoma Patients from a Large Multicenter Database

Abstract: Background Numerous predictive factors for cutaneous melanoma metastases to sentinel lymph nodes have been identified; however, few have been found to be reproducibly significant. This study investigated the significance of factors for predicting regional nodal disease in cutaneous melanoma using a large multicenter database. Methods Seventeen institutions submitted retrospective and prospective data on 3463 patients undergoing sentinel lymph node (SLN) biopsy for primary melanoma. Multiple demographic and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 45 publications
6
47
1
1
Order By: Relevance
“…It has recently been demonstrated that lymphovascular invasion is also strongly correlated with ulceration [8]. It is no surprise then that ulcerated melanomas show an increased sentinel lymph-node positivity rate in patients with melanomas more than 1 mm and also in patients with thin melanomas [9,10].…”
Section: Biologic Study Findingsmentioning
confidence: 99%
“…It has recently been demonstrated that lymphovascular invasion is also strongly correlated with ulceration [8]. It is no surprise then that ulcerated melanomas show an increased sentinel lymph-node positivity rate in patients with melanomas more than 1 mm and also in patients with thin melanomas [9,10].…”
Section: Biologic Study Findingsmentioning
confidence: 99%
“…Many studies have established the role of younger age, greater Breslow thickness, ulceration, and tumour mitotic rate in predicting SLN metastases [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter retrospective and prospective study, White et al [16] confirmed the synchronicity of Breslow thickness greater than 2 mm, ulceration, absence of regression, younger age, and trunk location as wellestablished predictive factors of lymph node involvement, and of lymphatic invasion as a less well-established variable. More recently, other means were put to test to assess the metastatic spread on the basis of the characteristics of the primary melanoma tumor such as the extent of lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Current studies are based on specific characteristics of the primary melanoma tumor [13][14][15][16][17][18] or on measurement of related serum biomarkers as an alternative to sentinel lymph node (SLN) biopsy [19,20].…”
Section: Introductionmentioning
confidence: 99%